Fences: Let'em Grow - William M. Giuliano (EDIS)
If you want to benefit many wildlife species on your property, build or improve your fencerows. No matter how big or small, let'em grow! This document is WEC 206 and one of a series of the Department of Wildlife Ecology and Conservation,UF/IFAS Extension. First published: May 2006.